2021
DOI: 10.2147/dmso.s308553
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Concordant Comorbidities and Associated Factors Among Adult Diabetic Out-Patients at Hiwot Fana Specialized University Hospital, Harar, Eastern Ethiopia: a Cross-Sectional Study

Abstract: Background: Nowadays diabetic comorbidities constitute a major public health problem in Ethiopian context. However, there is a dearth in epidemiology and risk factors of diabetic comorbidity in Ethiopia, particularly in the study setting. Therefore, this study was conducted to determine the prevalence and identify factors associated with concordant diabetic comorbidities among diabetic out-patients at Hiwot Fana Specialized University Hospital (HFSUH), EasternEthiopia. Methodology: A hospital-based cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 40 publications
4
17
1
Order By: Relevance
“…Comorbidity appeared as a correlate of glycemic control in this study. This finding was congruent with those of previous studies conducted in Ethiopia (60) and Croatia that reported the effect of comorbidities on the level of HbA1c (61). This might be because patients with a comorbid condition have less energy to have physical exercise, which likely lowers the blood glucose level (62).…”
Section: Discussionsupporting
confidence: 93%
“…Comorbidity appeared as a correlate of glycemic control in this study. This finding was congruent with those of previous studies conducted in Ethiopia (60) and Croatia that reported the effect of comorbidities on the level of HbA1c (61). This might be because patients with a comorbid condition have less energy to have physical exercise, which likely lowers the blood glucose level (62).…”
Section: Discussionsupporting
confidence: 93%
“…According to community-based studies, diabetes and hypertension prevalence among adults in Ethiopia ranged from 2.0 percent to 6.5 percent and 9.3% to 30.3%, respectively ( Guariguata et al, 2014 ; Dong et al, 2019 ). Approximately 42.3% of DM patients have hypertension as a comorbidity ( Ejeta et al, 2021 ). However, the overall prevalence of poor glycaemic control and uncontrolled hypertension in patients attending public health facilities was 45.2% and 48.6%, respectively ( Nigussie et al, 2021 ; Aberhe et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that various factors like sex, age, place of residence, economic status, duration of DM, family history of DM, type of DM, type of treatment, proteinuria, and glycemic control all influence the development of comorbidities in DM patients (6)(7)(8)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Concordant comorbidities are two or more diseases that have a comparable pathophysiological risk profile and a similar disease treatment plan as DM. whereas, conditions that are not etiologically related to DM and don’t share comparable risk factors are discordant comorbidities ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation